Relationships of climate and irrigation factors with malaria parasite incidences in two climatically dissimilar regions in India. (January 2016) - Lee, Eungul; Burkhart, John; Olson, Sarah; Billings, Anthony A.; Patz, Jonathan A.; Harner, E. James
Abstract: We examine how climate and irrigation conditions are associated with malaria infection from 1986 to 1995 in two climatically dissimilar regions in India. We analyze annually averaged malaria parasite incidence (API) and seasonally averaged climate and irrigation variables in western Rajasthan and Arunachal Pradesh. In arid western Rajasthan, API is significantly positively correlated with summer precipitation and soil moisture, and negatively correlated with summer potential evapotranspiration. Irrigation variables during boreal spring show a significant positive correlation with API in the moisture-limited region. In humid Arunachal Pradesh, API is positively related to summer temperature, but negatively related to summer precipitation and spring irrigation variables, while no statistically significant correlations are observed. During the years of high sea surface temperatures (SSTs) in the tropical western Pacific, increasing precipitation (accompanied by decreasing temperature) in northwestern India appears to promote malaria infection in arid western Rajasthan. However, during the same years, decreasing precipitation and increasing temperature result in increasing malaria incidence in humid Arunachal Pradesh. The statistically significant relationships of climate and irrigation factors with API in western Rajasthan suggest that increasing spring irrigation activity and wetter summer climates related to warmer SST in tropical western Pacific could increase malaria risk in the arid climate region. Highlights: Exploring the links between climate, irrigation and malaria in arid and humid India. Increased irrigation and the associated increase in malaria incidence in arid areas. Significant role of sea surface temperature in western Pacific in controlling malaria.